Rancang Bangun Sistem Informasi Rekam Medis Klinik Rawat Jalan Berbasis Web - Agung Suryadi; Yunita Wisda Tumarta Arif; Nur Syahbani No (Jurnal Infokes, 2022)
The world of health is currently experiencing very rapid progress both in developed and developing countries, the clinic is one of the service units engaged in the health sector, with the development of Science and Technology (IPTEK) in the health sector, health service providers are required to Providing effective and efficient services is an absolute requirement in order to achieve optimal service. One of the vital parts in health services is the medical record unit. In the recording of medical record documents, there are still many things that are done conventionally, resulting in delays in information, therefore a computerized/electronic recording method is needed. Medical record documents are made electronically to avoid lost documents, take up storage space, and avoid inconsistencies in filling out medical record documents. The completeness of the items contained in the medical record also greatly affects the quality of the information produced. The web-based medical record information system allows various information from various sources to be stored and processed and communicated to retrieve the processed results. By applying information technology in managing medical record data, it is able to provide convenience in managing medical record data to making the required reports. The purpose of this study is to create a web-based clinical medical record information system application and to find out the flow and procedures of a web-based clinical medical record information system, so that data and information can be stored and managed effectively and efficiently. This research is expected to provide convenience in recording medical records in outpatient clinics and can provide better services to be able to improve the quality of service to patients.